PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI EKSPOSITORIS DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK PADA SISWA KELAS VIII F SMP NEGERI 1 SELAT KUALA KAPUAS KABUPATEN KAPUAS - Melania Sugiyanti (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2016)
This recearch aims in writing expository narrative essay using the scientific approch (1) lesson planning Indonesian based scientific approach appropriate curriculum in class VIII F 2013 SMP Negeri 1 Strait Kuala Kapuas, (2) the implementation of llellaning Indonesian based scientific approch appropriate curriculum in class VIII F 2013 SMP Negeri 1 Strait, (3) evaluation of learning Indonesian appropriate scientific approach scientific approch appropriate curriculum in class VIII F 2013 SMP Negeri 1 Strait, and (4) the narrative Indonesia based scientific approach appropriate curriculum in class VIII F 2013 SMP Negeri 1 Strait Kuala Kapuas.The design of the study using a scientific approach in teaching writing method can evaluate and get a association betwee other language skills, including the study of case, 1) fist environmental factors, 2) intelligence, 3) personality learners, 4) the growth of learners, 5) maturity learners. The resuls of direct research because it has the implementation of the 1) curriculum organizational structure to establish the position of aspects of expository narative skills, 2) determination of material and svientific strategies in learning, 3) attitudes of teachers in teaching, 4) the attitude of teachers in addressing the difficulties faced by learners in ekspositoris naarative writing process, 5) thr determination of the type of learners.The results showed that (1) in the fifth stage of the learning plan the mainn activities planned scientific approach to the commponent measures of learning, 2) in the fifth stage of the implementation of the main activities andd implemented in two or three meeting, 3) in the assessment of learning evaluation phase includes assesing aspects of knowledge and skills, and 4) the constraints experienced by teachers is a discrepancy text structure, keruntutan exposure , use sentences, vocabulary, penerikan title, and use EYD in writing of learners.